CONTAMINACIÓN POR ENTEROPARASITOS EN HORTALIZAS EXPENDIDAS EN MERCADOS DE LA CIUDAD DE MÉRIDA, VENEZUELA. - García Labrador, Ligia Esperanza; Navas, María; Camacaro Garda, Lilian Paula; Castro, Trino Alberto; Hernández, Morelia; Salinas, Pedro José (MedULA)
To determine the presence of parasites in vegetables sold in the markets of the city of Mérida (Venezuela). The vegetables that presented the greater percentage of contamination were: radish, small onion and carrot. An analytical study was made. 120 samples of 10 types of vegetables coming from the three most important markets of the city of Mérida were analyzed. The selection of the samples was made randomly. At each market 4 samples of each vegetable were taken. It was observed with saline solution and lugol. Parasites were found in a 11.67% of the samples collected. Helmintos were found in a 78.58% of the samples. Conclusions: The isolated helmints found were: larvae of nematodes and Toxocara sp. The isolated protozoon found were: Blastocystis hominis, and Entamoeba sp.. The vegetables that presented the greater percentage of contamination were: radish, small onion and carrot.